Electrochemical performance of Bi2O2CO3 nanosheets as negative electrode material for supercapacitors. Issue 12 (15th August 2017) - Wang, Bo; Wang, Jingyi; Zhang, Yan; Mei, Yi; Lian, Peichao
Abstract: Bi2 O2 CO3 was firstly prepared by using a gas-liquid interfacial synthesis approach. The crystalline structure and morphology of the Bi2 O2 CO3 were characterized by X-ray diffraction, Fourier transform infrared spectra, scanning electron microscopy and transmission electron microscopy. The electrochemical performance was investigated by using cyclic voltammetry and galvonostatic charge-discharge tests in KOH solution. The characterization results of the X-ray diffraction, Fourier transform infrared spectra, scanning electron microscopy and transmission electron microscopy indicate that Bi2 O2 CO3 nanosheets were formed during the gas-liquid interfacial reaction process. The electrochemical test results show that the Bi2 O2 CO3 nanosheets possess high specific capacitance, good rate capability at negative potential. The specific capacitance of the Bi2 O2 CO3 nanosheets is as high as 1045.3 F g −1 at a specific current of 1 A g −1 . Even at the high specific current of 20 A g −1, the Bi2 O2 CO3 nanosheets still can deliver a specific capacitance of 714.4 F g −1 . In order to understand the electrochemical action of the Bi2 O2 CO3, the fully discharged and charged Bi2 O2 CO3 electrodes were characterized by using X-ray diffraction and X-ray photoelectron spectroscopy. Surprisingly OH - can reversibly intercalate into and deintercalate from layered Bi2 O2 CO3 with valence conversions of bismuth during charge and discharge process.